Pemberdayaan Generasi Muda Muslim Lewat Pemberian Materi Dakwah Terprogram Berbasis Teologi Islam Rasional - Sutriyono, Sutriyono; Hidayat, Ahmad (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2025)
EMPOWERMENT OF YOUNG MUSLIMS THROUGH THE PROVISION OF PROGRAMATIC DA'WAH MATERIAL BASED ON RATIONAL ISLAMIC THEOLOGY. Community empowerment mostly uses economic, legal, gender equality, and environmental approaches to build community awareness so that they dare to rise up and change the circumstances that hinder their development, progress, and prosperity. On the other hand, the potential of Islamic teachings as a guide to life can be used as an approach that is no less important than other empowerment approaches. Islamic teachings, which are teachings for community development, can serve as a new approach to community empowerment. On the other hand, the potential of the young Muslim generation as the successors of the development of the ummah and the nation must be the focus of efforts to regenerate a nation. This article offers an approach to empowering the young generation (gen Z) of Muslims who emphasize awareness by providing programmatic da'wah materials based on Rational Islamic theology that do not yet exist or have not been developed. This study uses descriptive qualitative methods based on related references. The study results show that rational Islamic theology can be an approach in empowering the community, especially the young generation of Islam. The approach of providing programmatic da'wah materials based on rational Islamic theology that emphasizes aspects of divine, moral and social awareness that can encourage individual or community awareness to understand the purpose, direction and meaning of life so that they can improve themselves towards a better direction and also have social roles in society.